2017
DOI: 10.1667/rr14656.1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Dysregulation after Neutron Exposures Expected from an Improvised Nuclear Device

Abstract: The increased threat of terrorism across the globe has raised fears that certain groups will acquire and use radioactive materials to inflict maximum damage. In the event that an improvised nuclear device (IND) is detonated, a potentially large population of victims will require assessment for radiation exposure. While photons will contribute to a major portion of the dose, neutrons may be responsible for the severity of the biologic effects and cellular responses. We investigated differences in response betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 49 publications
(57 reference statements)
5
36
0
Order By: Relevance
“…In addition, we identified pathways related to amino acid and fatty acid oxidation to be among the significantly underrepresented pathways in the 83% neutron exposure. This finding is in agreement with recently published metabolomics data that compared x-rays to neutron radiation and found that neutrons induced a severe metabolic dysregulation, with perturbations predominantly in amino acid metabolism and fatty acid β-oxidation [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we identified pathways related to amino acid and fatty acid oxidation to be among the significantly underrepresented pathways in the 83% neutron exposure. This finding is in agreement with recently published metabolomics data that compared x-rays to neutron radiation and found that neutrons induced a severe metabolic dysregulation, with perturbations predominantly in amino acid metabolism and fatty acid β-oxidation [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Blood is one of the most commonly used biofluids for any sort of testing, and is an obvious choice to investigate for metabolites that may assist in dose reconstruction, injury diagnosis, and prognosis. Indeed, blood metabolomic markers may be able to distinguish the type of radiation one is exposed to, as was found when mice were exposed to X-ray vs. neutron radiation [36]; or determine specific organ injury, as Jones et al found when studying small intestine tissue metabolites compared to plasma metabolites of mice exposed to TBI [114]. Importantly, some metabolite signatures, including increases in polyunsaturated fatty acid-containing lipids, have been consistently found across mice [115,116], NHPs [26,117], and humans [118], over a range of radiation doses.…”
Section: Bloodmentioning
confidence: 95%
“…In the case of both sources, changes in metabolites such as citrulline, citric acid, creatine, taurine, carnitine, xanthine, creatinine, hypoxanthine, uric acid, and threonine were consistently observed ( Table 2). Using a neutron source that simulates an exposure similar to that in Hiroshima at 1-1.5 km from the epicenter, investigators demonstrated a severe metabolic dysregulation, with perturbations in amino acid metabolism and fatty acid β-oxidation in irradiated mice [36]. Urinary metabolites were able to discriminate between neutron and X-rays on day 1, as well as day 7 post-irradiation.…”
Section: Variability Due To Irradiation Sources and Animal Model Selementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high relative biological effectiveness of neutrons for causing cytogenetic damage [9][10][11] , the neutron dose contributes roughly 4 times the damage of an equivalent photon dose. Consequently, these neutron components are likely to have a profound impact on disease type and progression [12][13][14][15] . It is also likely that different countermeasures will be required for neutroninduced disease and photon-induced exposure 16 Significance of partial body exposures A significant proportion of individuals exposed indoors to the initial blast from an IND will be exposed non-homogeneously, to a partial body exposure, due to shielding by objects and building materials 7 .…”
Section: Significance Of Neutronsmentioning
confidence: 99%